The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

Taxing the digital economy: Options available for African countries - Oluwatuyi, Oluwasikemi (University of Victoria, 2024)
Tax authorities have always assessed and enforced taxes based on the physical address of businesses over the years. Nevertheless, the idea of tax jurisdiction has taken on a new meaning with the development of information and communication technology, and its profound impact on every facet of human existence – including but not restricted to trade and business. This development has undoubtedly increased capital mobility, especially in corporate form, and exposed more the weaknesses in national tax laws by enabling the artificial relocation of important economic components and potential exemption from taxes. Since it is getting harder to separate the digital economy from the rest of the economy for taxation reasons, the process of digitalization has emerged as one of the primary growth drivers. This expansion, together with aggressive tax planning strategies used by multinational enterprises (MNEs) to move revenues to low-tax jurisdictions and the development of business models requiring less physical presence, has increased the workload for tax administrators; furthermore, it has reduced governments’ capacity to raise funds in the traditional manner. In this regard, I assess how “adequate” the selected African countries’ frameworks are vis-à-vis the ongoing OECD and UN negotiations. Beyond the consultations, I call for a more inclusive and Africanised approach and the need for African countries to improve their tax administration mechanisms.
https://hdl.handle.net/1828/20312
Keywords: Digital economy; International taxation; OECD; Tax

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

Strategies adopted by Commercial Banks in Kenya in Response to the Law Capping Interest Rates - Ragor, Rodgers Kiptoo (University of Nairobi, 2017)
The ability of an organization to adjust its operation in light of the evolving changes in their operating environment determines the sustainability of the business unit in both the short and long term. The objective of the study was to determine the response strategies adopted by Kenyan commercial banks in response to the interest capping laws. A descriptive cross-sectional design was used. The population of the study was 42 commercial banks operating in Kenya. Primary data was collected using a questionnaire that was both closed and open ended. Data was analysed using the descriptive statistics. The study found that banks have employed adaptation strategies through working with other partners in the banking sector to leverage their synergy and concentrate on areas that enhance competitive advantage. The research findings also reinforced the need for the banks to work together as a sector and attempt and change the laws that inhibit their operations through lobby groups in parliament and other forums. The study also show that there exists a link between firms‟ strategic activities and their strategic responses and therefore, bank managers should diversify their product range especially to the youth who are apt in using the mobile technology to access services and improve the bank level of efficiency and effectiveness in their operations. The study recommends that the commercial banks ought to conform to the regulations to attract customers while the Central Bank as a regulator should likewise be sensitive to the operating environment and should be flexible in setting the rules in order to attract investment and support the growth in the banking industry. The Interest capping law is still at its infancy stage in Kenya and thus there is room for further research as the full impact of the law is realized in the long term.